Similar anxiolytic-like effects following intra-amygdala infusions of benzodiazepine receptor agonist and antagonist: Evidence for the release of an endogenous benzodiazepine inverse agonist in mice exposed to elevated plus-maze test - Barbalho, Cilene Aparecida; Nunes-de-Souza, Ricardo L. [UNESP]; Canto-de-Souza, Azair (Elsevier B.V., 2009)
Previous studies have demonstrated that microinjections of midazolam, a benzodiazepine receptor agonist, into the amygdala produce anxiolytic-like effects in elevated plus-maze (EPM)-naive rodents. However, systemic or intracerebral administration of benzodiazepines (BDZ) fails to alter anxiety in maze-experienced animals, a phenomenon defined as one trial tolerance (OTT). This study focused on the effects of intra-amygdala infusion of midazolam in maze-experienced mice. In addition, the effects of flumazenil in the amygdala of maze-naive and experienced mice were also investigated. To investigate intrinsic effects of intra-amygdala flumazenil on anxiety, animals were systemically treated with the BDZ receptor inverse agonist, DMCM (4-ethyl-6,7-dimethoxy-9H-pyrido[3,4-b] indole-3-carboxylic acid methyl ester hydrochloride). Conventional measures of anxiety (% open arm entries and % open arm time), locomotor activity (frequency of closed arm entries) and a range of ethological measures related to risk assessment were recorded. Intra-amygdala midazolam (3.0 and 30 nmol) attenuated anxiety in maze-experienced mice. A similar behavioral profile was produced by intra-amygdala flumazenil in maze-naive (4.0 and 16 nmol) and maze-experienced (16 nmol) mice. Intra-amygdala flumazenil (at 2.0 nmol, a dose devoid of any intrinsic effect on anxiety measures in the EPM) selectively and completely blocked the anxiogenic-like effects of systemic administration of DMCM (1.0 mg/kg, i.p.) in maze-naive mice. Together, these results demonstrate that the GABA(A)-benzodiazepine receptor complex located within the amygdala does not play a role in the OTT phenomenon. Present results also suggest that the release of an endogenous BDZ receptor inverse agonist within the amygdala seems to be an important correlate of the emotional state induced by the plus-maze test. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Anxiety; Maze-naive and maze-experienced mouse; Midazolam; Flumazenil; DMCM; Amygdala